A participant observation study of the resolution of audit engagement challenges in government tax compliance audits. Issue 4 (11th November 2014) - Richard Baker, Dr; Stephan Hayes, Rick; Baker, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aim of this paper is to extend the prior auditing literature by examining audit engagement challenges arising during government tax compliance audits. The prior auditing literature has examined how audit engagement challenges have been resolved through auditor/auditee negotiations. Design/methodology/approach – The empirical evidence for the paper was gathered during a participant observation study conducted by the primary researcher over a period of six years while working as an auditor for the Alcohol and Tobacco Tax and Trade Bureau (TTB) of the US Department of Treasury. Findings – This paper discusses various challenges faced by government auditors and how these challenges were resolved. The path to resolution was not always clearly marked. Resolution depended a great deal on the individual auditor's judgment, interpretation of the Code of Federal Regulations (CFRs), and the willingness of the auditee to change the methods and techniques they use in operating and reporting wine operations. Materiality was determined by compliance with the regulation criteria [CFRs and the US Code (USC)] – any non-compliance was considered to be material. Resolution of many of the challenges resulted in an increased payments of excise taxes or penalties by the auditee entities. In other cases, the audit agency allowed the auditees to agree to change or amend their practices to correct a violation or a lack of compliance with US federal government regulations. As such, while the difference in the role and status of the government tax compliance auditor as compared with the independent external auditor did not necessarily lead to a different set of audit procedures, the pattern of communications between the auditor and the auditee in a government tax compliance audit were quite different from an external audit of financial statements. The government tax compliance environment is often complex, but the auditor may draw on a number of sources of knowledge and communication: CFRs, USC, Generally Accepted Government Auditing Standards, national audit planning, national experts, winery management, local peers, local government supervision, legal counsel and other auditors. Originality/value – The primary contribution of the paper lies in the fact that little or no prior research in auditing has been conducted using participant observation as a research methodology. The use of participant observation provides new perspectives on the resolution of audit engagement challenges and auditor/auditee communication and negotiation.